Estimates of absolute crown strength and bite force in the lower postcanine dentition of Gigantopithecus blacki. Issue 175 (February 2023) - Yi, Zhixing; Zanolli, Clément; Liao, Wei; Wang, Wei
Abstract: Gigantopithecus blacki is hypothesized to have been capable of processing mechanically challenging foods, which likely required this species to have high dental resistance to fracture and/or large bite force. To test this hypothesis, we used two recently developed approaches to estimate absolute crown strength and bite force of the lower postcanine dentition. Sixteen Gigantopithecus mandibular permanent cheek teeth were scanned by micro-computed tomography. From virtual mesial cross-sections, we measured average enamel thickness and bi-cervical diameter to estimate absolute crown strength, and cuspal enamel thickness and dentine horn angle to estimate bite force. We compared G. blacki with a sample of extant great apes ( Pan, Pongo, and Gorilla ) and australopiths ( Australopithecus anamensis, Australopithecus afarensis, Australopithecus africanus, Paranthropus robustus, and Paranthropus boisei ). We also evaluated statistical differences in absolute crown strength and bite force between the premolars and molars for G. blacki . Results reveal that molar crown strength is absolutely greater, and molar bite force absolutely higher, in G. blacki than all other taxa except P. boisei, suggesting that G. blacki molars have exceptionally high resistance to fracture and the ability to generate exceptionally high bite force. In addition, G. blacki premolars have comparable absolute crown strength and larger bite force capabilities compared with its molars, implying possible functional specializations in premolars. The dental specialization of G. blacki could thus represent an adaptation to further facilitate the processing of mechanically challenging foods. While it is currently not possible to determine which types of foods were actually consumed by G. blacki through this study, direct evidence (e.g. dental chipping and microwear) left by the foods eaten by G. blacki could potentially lead to greater insights into its dietary ecology.